IMC APPROACH IN PHYSICAL EDUCATION CLASSES OF ELEMENTARY SCHOOL IN THE CITY OF AL-TEOTONIO VILELA. (Fiep Bulletin - online, 2011)
Obesity is one of the evils that grows more in the world, given that the World Health Organization (WHO), adopted the BMI as the calculation of ideal weight for each individual. This study aims to identify how the professionals in the city of Fitness Teotônio Vilela deal with issues related to health and particularly BMI. A study of field of qualitative approach for this type of research that is descriptive, using a questionnaire to better analysis of the subject. Because the way was prepared the annual plan, the teachers of Physical Education were unable to tackle the issues mentioned. However, through lectures conducted every two months, teachers seek to fill the gap that is undoubtedly essential for the formation of the individual.
Keywords: obesity; approach; scope; gap